Immortalized Schwann cell lines as useful tools for pathogenesis-based therapeutic approaches to diabetic peripheral neuropathy - Sango, Kazunori; Yako, Hideji; Niimi, Naoko; Takaku, Shizuka (Frontiers in Endocrinology, 2025)
Growing evidence suggests that hyperglycemia-related abnormalities in Schwann cells play a pivotal role in the development and progression of diabetic peripheral neuropathy (DPN). Several immortalized Schwann cell lines have been established in our laboratory and utilized for the study of DPN; IMS32 from normal ICR mice, 1970C3 from normal C57BL/6 mice, IWARS1 and IKARS1 from wild-type and aldose reductase-deficient C57BL/6 mice, and IFRS1 from normal Fischer 344 rats. These cell lines retain biological features of Schwann cells and display high proliferative activities that enable us to perform molecular and biochemical analyses. In addition, these cells have exhibited metabolic alterations under exposure to diabetes-associated conditions, such as hyperglycemia, dyslipidemia, glycative and oxidative stress load. Herein, recent studies with these cell lines regarding the pathogenic factors of DPN (augmentation of the polyol and other collateral glycolysis pathways, glycative and oxidative stress-induced cell injury, autophagic and proteostatic disturbances, etc.) and therapeutic strategies targeting these factors are introduced.